Clarifying the influence of sport education on basic psychological need satisfaction in high school students - Rafael Burgueño; Belén Cueto-Martín; Esther Morales-Ortiz; Payla Cristina Silva; Jesus Medina-Casaubón (Desafio Singular, 2018)
Based on Self-Determination Theory, this research aimed to examine la influence of Sport Education on basic psychological need satisfaction in the sport teaching-learning process that takes place in Physical Education. The participants were 44 high school students (22 men and 22 women; Mage = 16.32, SDage = 0.57) and 2 Physical Education pre-service teachers. The design was a quasi-experimental study with, a priori, non-equivalent control group using pre- and post- intervention measures and intra- and inter- analyses. The intervention consisted of 12 basketball sessions both for the experimental group (n = 22), which developed Sport Education, and for the control group (n = 22), which developed the traditional teaching. The results showed that Sport Education significantly improved the levels of autonomy, competence and relatedness need satisfaction in the inter-group analysis and in the intra-group analysis. In its conclusion, the suitability of Sport Education to contribute developing students' basic psychological need satisfaction in the sport teaching-learning process in Physical Education was indicated.